ANALISIS KELEMBAGAAN PENYULUHAN PERTANIAN DI PROVINSI RIAU - Syabrina, El; Hakim, Dedi Budiman; Tonny, Fredian (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2013)
Varied institutions responsible for agricultural extension in Riau Province have certainly run independently and caused the agricultural extension unproductive, ineffective, and inefficient. This study aims: 1) To identify the structure of agricultural extension institutions in the regional autonomy era in the Riau Province; 2) To analyze the implementation of agricultural extensions in different institutions, 3) To analyze the effect of different extension implementation on the performance of extension workers and the degree of technological application among farmers. This research was conducted from March-April 2008 in Pekanbaru, Kampar Regency and Pelalawan Regency. Methods used in this study were internal and external factors analysis, SWOT analysis (Strengths-Weakness-Opportunities-Threats), and QSPM analysis (Quantitative Strategic Planning Matrix). Result showed that: 1) Implementation of Laws Number 22/1999 and Number 32/2004 along with the regulations under the laws had caused the agricultural extensions in the Province of Riau to experience coevolution in the social infrastructure of agricultural extensions; 2) The functions of services and arrangement still dominate the working system of extension; 3) The frequency of LAKU is not fully implemented yet, and 4) Formulated strategy in developing the agricultural extension institutions in the Province of Riau is to form a separate and specific institution that regulates agricultural extension.Keywords: Agriculture, Extension, Institution, Riau Province, Strategies